Interleukin 10 gene promoter polymorphism –819 T/C modulates IL-10 levels independently of PGE2 in multibacillary leprosy - Fitriyanti; Lipinwati; Attiya Istarini; Tia Wida Ekaputri; Niken Irfa Nastiti; I Made Dwi Mertha Adnyana; Rini Pratiwi (KHD-Production, 2026)
The IL-10 –819 T/C promoter polymorphism influences cytokine production in leprosy, yet its functional interplay with serum IL-10 and prostaglandin E2 (PGE2) in Indonesian populations remains undefined. This study investigated its association with multibacillary (MB) leprosy susceptibility and systemic mediator levels. In a case–control design, 35 MB patients and 35 healthy controls from Banyuasin Regency, South Sumatra, were enrolled. PCR-RFLP was used for genotyping, and ELISA was used to quantify serum IL-10 and PGE2. Genotype and allele frequencies did not differ between groups (OR = 1.121; 95% CI: 0.439–2.863; p = 0.811), indicating no susceptibility effect. Serum IL-10 was significantly elevated in patients (median 2.15 pg/mL) versus controls (1.23 pg/mL; p = 0.033). Within cases, IL-10 exhibited a C-allele dose-dependent gradient (TT: 3.82; CT: 4.96; CC: 16.20 pg/mL), though statistically underpowered (H = 0.452; p = 0.798). PGE2 showed no intergroup differences (p = 0.142), nor correlations with genotype (p = 0.915) or IL-10 (rₛ = −0.057; p = 0.639). The IL-10 –819 T/C variant does not predict MB susceptibility but, in a pathogen-context-dependent manner, functionally amplifies IL-10 production. This genetic effect operates independently of systemic PGE2 regulation, highlighting distinct immunomodulatory pathways and supporting the CC genotype as a potential biomarker of immune-suppression severity.